Laforin, a dual specificity phosphatase involved in Lafora disease, is present mainly as monomeric form with full phosphatase activity. - Vikas V Dukhande; Devin M Rogers; Carlos Romá-Mateo; Jordi Donderis; Alberto Marina; Adam O Taylor; Pascual Sanz; Matthew S Gentry (PLoS ONE)
Lafora Disease (LD) is a fatal neurodegenerative epileptic disorder that presents as a neurological deterioration with the accumulation of insoluble, intracellular, hyperphosphorylated carbohydrates called Lafora bodies (LBs). LD is caused by mutations in either the gene encoding laforin or malin. Laforin contains a dual specificity phosphatase domain and a carbohydrate-binding module, and is a member of the recently described family of glucan phosphatases. In the current study, we investigated the functional and physiological relevance of laforin dimerization. We purified recombinant human laforin and subjected the monomer and dimer fractions to denaturing gel electrophoresis, mass spectrometry, phosphatase assays, protein-protein interaction assays, and glucan binding assays. Our results demonstrate that laforin prevalently exists as a monomer with a small dimer fraction both in vitro and in vivo. Of mechanistic importance, laforin monomer and dimer possess equal phosphatase activity, and they both associate with malin and bind glucans to a similar extent. However, we found differences between the two states' ability to interact simultaneously with malin and carbohydrates. Furthermore, we tested other members of the glucan phosphatase family. Cumulatively, our data suggest that laforin monomer is the dominant form of the protein and that it contains phosphatase activity.